Pengaruh Hedonic Shopping Value dan Sales Promotion Terhadap Impulse Buying Dengan Emosi Positif Sebagai Variabel Mediasi (Studi Pada Pengguna Tokopedia) - Vinka Noerviana; Widyastuti Widyastuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Impulse buying occurs when consumers experience a sudden urge, often strong and continuously to buy something as soon as possible Impulse buying can be influenced by internal and external factors such as hedonic shopping value and sales promotion This study aims to discuss the effect of hedonic shopping value and sales promotion on impulse buying with positive emotions as a mediating variable Study on Tokopedia Users. This is a quantitative study that used judgmental sampling techniques on 210 respondents. The questionnaires were distributed online, and responses were measured using the Likert scale. The statistical analysis used was path analysis using the AMOS application. The results showed that hedonic shopping value, sales promotion, and positive emotions affect impulse buying. Furthermore, hedonic shopping value and sales promotion affect positive emotions. In addition, positive emotions mediate the relationship between hedonic shopping value, sales promotion, and impulse buying.